2006
DOI: 10.1007/s11062-006-0057-3
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive effects of low-intensity extrahigh-frequency electromagnetic radiation

Abstract: We studied the effect of low-intensity extrahigh-frequency (EHF) electromagnetic radiation (EMR) on changes of behavior phenomena in rats observed under conditions of experimentally induced tonic somatic, visceral, and acute thermal pain. Preliminary irradiation of the animals with EHF EMR was found to exert clear antinociceptive effects. Decreases in the intensity of pain reactions were observed under conditions of both single and repeated irradiation sessions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 4 publications
1
14
0
Order By: Relevance
“…In our earlier study [9], we found that low-intensity EHF EMR also possesses a clearly pronounced antinociceptive action in pain stresses of different etiologies (experimentally induced tonic, visceral, and acute thermal pain). However, the mechanisms underlying this phenomenon have been interpreted only hypothetically.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…In our earlier study [9], we found that low-intensity EHF EMR also possesses a clearly pronounced antinociceptive action in pain stresses of different etiologies (experimentally induced tonic, visceral, and acute thermal pain). However, the mechanisms underlying this phenomenon have been interpreted only hypothetically.…”
Section: Introductionmentioning
confidence: 79%
“…Influences of this factor are widely used in medical practice for the treatment of various diseases [1][2][3][4]. It was demonstrated that the action of EHF EMR provides anti-stress, immunomodulating, anti-oxidant, anti-inflammatory, radioprotective, and a number of other effects; it also synchronizes rhythmic biological processes [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Considering possible mechanisms, which are in charge for EMR SHF antiepileptic effects, it should be mentioned that involvement of serotoninergic and histaminergic receptor-depended mechanisms in the development of antinociceptive effects of EMR EHF has been established [1,5]. Besides, transcutaneus action of EMR EHF activated endogenous opioid system and precipitated analgesic action [2].…”
Section: Discussionmentioning
confidence: 99%
“…Taking into consideration the experimental conditions, absorbed dosage of emitted energy did not exceed 0,05-0,1 J per animal, when 15,0 min exposition of EMR was performed. Hence, EMR did not induce thermal effect, which is quite characteristic for an action of such type of irradiation [1,5,6]. Hence, under such conditions the absence of thermal effects of such influence was expected [18].…”
Section: Emr Ehf and Hypogeomagnetic Influencesmentioning
confidence: 99%
See 1 more Smart Citation